COACHING - CHALLENGES AND OPPORTUNITIES IN A MODERN VOCATIONAL EDUCATION - Kuk, Tomasz (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
The article pays attention to the changing role of the teacher of vocational school in modern conditions through the use of instruments of coaching. Specifically: on the counterweight of the approach to the student, the teacher should develop ability to learn, new thinking strategies and actions thus obtaining a much better end results; provoke to meet new situations not focusing on improving existing ones. The teacher should get it through the creation and modeling situations to place students in new situations with new external information. Besides modern teacher should provoke a stronger feeling of the situation and inspire students of vocational schools to make their own decisions, giving them the opportunity to get in the end the professional who is able to make independent and responsible decisions in their professional work. We believe that the instruments of coaching (changing of optics, using the Dilt’s pyramid, provocative and deepen questions) allow the implementation of all the above assumed tasks and functions of a modern teacher in vocational education and training. The results of research which dealt with students’ self estimation of their strengths and weaknesses which should effect their willingness to learn and in the future – their professional performance – are presented in the article.